Examining Undergarment Preferences During Confinement Period towards Designing Caesarean Undergarment Design for Plus-Size Patients - Osman, Juliana; Mohd Tajuddin, Rosita; Omar, Noorkardiffa Syawalina; Mohd Shariff, Shaliza (Environment-Behaviour Proceedings Journal, 2023)
A purposive sampling method on experienced Malaysian plus-size patients with a BMI of 30 to 40 and aged between 20 to 49 years old was conducted to investigate the preferences of undergarment design used during the confinement period and the influencing factors of clothing comfort throughout the recovery period. Results show that although 89.29% of respondents practised traditional confinement rituals, 93% of respondents preferred basic undergarments as opposed to compression garments due to the existence of an apron belly. Based on the result, a theoretical framework for plus-size caesarean undergarment design was developed.